Kaidah Qira’at Imam Nafi’ Riwayat Warsy dan Penerapannya di Pondok Pesantren Tahfidzul Qur’an Putri Al-Lathifiyyah Palembang - Lailatul Mu'jizat (Al-Dirayah, 2020)
Volume 6, Nomor 2, Tahun 2020Kaidah Qira’at Imam Nafi’ Riwayat Warsy dan Penerapannya diPondok Pesantren Tahfidzul Qur’an Putri Al-Lathifiyyah PalembangLailatul Mu’jizatSekolah Tinggi Ilmu Al-Qur’an Al-Lathifiyyah PalembangEmail: lailatulmukjizat70@gmail.comABSTRACTThis research is motivated by the emergence of Qira'at knowledge which mustbe studied and practiced so that it is not lost and considered foreign by Muslims. Thistype of research is a field research (field research). While the type of data used isqualitative data. Sources of data used in this study are primary data sources andsecondary data sources. In analyzing data using three procedures, namely datareduction, data presentation, and data verification or drawing conclusions. Qira'at is ascience that studies the different ways of pronouncing al-Qur'an which is adopted byone of the Imams based on the sanad-sanad which is continued to the ProphetMuhammad. In order to carry out the teachings of the Prophet, the leadership of theAl-Lathifiyyah Islamic Boarding School for the daughter of Al- Lathifiyyah inPalembang carried out the agenda of grounding the Qira'at, in this case the Qira'atImam Nafi 'History of Warsy. There are several things that become the reference forthis research, namely: What is the rule of Qira'at Imam Nafi from Warsy?, how are theefforts to implement the Qira'at Imam Nafi History of Warsy at Pondok PesantrenTahfizhul Qur'an Putri Al-Lathifiyyah Palembang? And what are the problemsexperienced by students in understanding Qira'at Imam Nafi, according to Warsy inthe Islamic boarding school Tahfizhul Qur'an Putri Al-Lathifiyyah Palembang ?. Theresults of this study concluded that the rules of Qira'at Imam Nafi from Warsy's historywere to use the ushuliyyah rule and the Farsyul letter rule. Meanwhile, the applicationof the learning process of Qira'at Nafi 'in Warsy's history is to use a variety of readingBi al-ifrad (Mufrod Method), namely Qori' reading qira'at by specifying the variety ofreadings from one narration. The history used is Imam Nafi's history 'Warsy's history.Talaqqi and sima'i systems and with a Tadwir tempo. The problems experienced bySantriwati in Qira'at learning at the Tahfidzul Qur'an Putri Al-Lathifiyyah IslamicBoarding School in Palembang include: shortness of breath, due to age, lack of interestin learning Qira'at, laziness, difficulties in the rules and limited time in learningQira'at.